2011
DOI: 10.5380/rf.v41i1.21174
|View full text |Cite
|
Sign up to set email alerts
|

Análise Da Ocorrência De Erva-De-Passarinho Na Arborização Da Universidade Federal De Sergipe, Campus São Cristóvão

Abstract: ResumoEste trabalho teve como objetivo analisar a ocorrência de erva-de-passarinho na arborização do campus da Universidade Federal de Sergipe, município de São Cristóvão. Para tal, todas as árvores foram identificadas, assim como as hemiparasitas. Fatores como a altura das árvores com ocorrência de hemiparasitas e o grau de infestação foram verificados. Constatou-se a presença de erva-depassarinho em 8,15% das árvores. A infestação ocorreu em quatro plantas exóticas -Azadirachta indica A. Juss., Casuarina equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 7 publications
2
3
0
3
Order By: Relevance
“…Another factor that interferes on mistletoe success is the size of the host plant. Our results are consistent with recent studies that demonstrated that larger hosts are more frequently attacked by mistletoes White et al 2011). Thies et al (2003) also reported that the effects of parasitism depend on the size, intensity, growth, metabolism and photosynthetic capacity of mistletoe, as well as the host development.…”
Section: Discussionsupporting
confidence: 93%
“…Another factor that interferes on mistletoe success is the size of the host plant. Our results are consistent with recent studies that demonstrated that larger hosts are more frequently attacked by mistletoes White et al 2011). Thies et al (2003) also reported that the effects of parasitism depend on the size, intensity, growth, metabolism and photosynthetic capacity of mistletoe, as well as the host development.…”
Section: Discussionsupporting
confidence: 93%
“…The four most abundant host species in the survey had generally low crown infestation intensity by P. theloneura, which corroborates results of other studies of mistletoes in urban afforestations in Brazil (Leal et al 2006;White et al 2011). Low infestation intensity allows control using lowcost methods, such as manual removal and pruning, which are unlikely to damage the host trees (White et al 2011).…”
Section: Discussionsupporting
confidence: 86%
“…Low infestation intensity allows control using lowcost methods, such as manual removal and pruning, which are unlikely to damage the host trees (White et al 2011). Observations made in our study area, however, suggest that, if management is not frequent, P. theloneura can cover the entire canopy of the tree, a build-up that can lead to eventual host death.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…As ervas-de-passarinho são conhecidas principalmente pela ação nociva que provocam aos hospedeiros e pelo prejuízo a silvicultura, agricultura (principalmente nas plantações de cítricos) e também diminuindo a qualidade da arborização urbana (TORRES & MONTILLA, 1997;ROTTA, 2001;LEAL et al 2006;MATHIASEN et al, 2008;WHITE et al 2011, PEREIRA, 2014.…”
unclassified